Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.4085/1062-6050-209-18
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Athletic Trainers on the Incidence and Management of Concussions in High School Athletes

Abstract: Context In many US high schools, the athletic trainer (AT) has the responsibility to identify and manage athletes with concussions. Although the availability of ATs varies a great deal among schools, how the level of AT availability in high schools affects the reported incidence and management of sport-related concussions (SRCs) is unknown. Objective To determine how the presence of an AT affects the reporting and management … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 31 publications
0
39
0
Order By: Relevance
“…9 Although these investigations highlight the challenges of diagnosing patients with concussions, the presence of ATs was associated with increases in the diagnosis rate and the implementation of safe return-to-play protocols. 10 Coaches believed it was more acceptable to allow athletes to continue playing after a concussion, depending on the importance of the event, than to disqualify them from further participation. 11 The disconnect between coaches' beliefs and current best practice for a patient with concussion 12 provides grounds for organizational conflict.…”
mentioning
confidence: 99%
“…9 Although these investigations highlight the challenges of diagnosing patients with concussions, the presence of ATs was associated with increases in the diagnosis rate and the implementation of safe return-to-play protocols. 10 Coaches believed it was more acceptable to allow athletes to continue playing after a concussion, depending on the importance of the event, than to disqualify them from further participation. 11 The disconnect between coaches' beliefs and current best practice for a patient with concussion 12 provides grounds for organizational conflict.…”
mentioning
confidence: 99%
“…1 Overall, nearly 8 million student-athletes participate in high school athletics, which makes availability and access to athletic trainer (AT) services at the US secondary school level vital to ensuring prompt and appropriate medical care. 2 Researchers [3][4][5][6][7] have indicated that access to ATs at the secondary school level results in a variety of positive health outcomes, including reduced injury rates and improved recognition and management of various sport-related injuries, such as acute musculoskeletal injuries, recurrent injuries, and concussions. In addition to positive health outcomes, secondary schools with ATs are more likely to have emergency action plans, heat-illness policies, and automated external defibrillators, all of which greatly reduce the risk of catastrophic injury and death among student-athletes.…”
mentioning
confidence: 99%
“…Meehan 13 suggests that trained observer data are significantly higher than self-reported data. McGuine 17 determined that the reporting of concussions increases from schools with low-to medium-to high-level access of on-site athletic trainers. Only 50% of those athletes with low access to an athletic trainer followed a return to play protocol.…”
Section: Unreported Injuriesmentioning
confidence: 99%
“…Sport-related concussions (SRCs) have been at the forefront of sport medical concerns at all levels of sport. Concerns are especially focused on children aged [10][11][12][13][14][15][16][17][18][19] given their high prevalence of concussions 1 and considering the importance of this time period with respect to brain development. 2 The increasing awareness of chronic traumatic encephalopathy (CTE) has added to the concern about the long-term implications on quality of life in later years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation